New Life for Cold Fusion - Bauer, Henry (Journal of Scientific Exploration, 2020)
The take-away from this discussion is that research on nuclear reactions occurring at ordinary temperatures at certain metals in electrolysis in heavy water, which has been widely denigrated for three decades as “pathological science”, has now been recognized as a respectable topic for further research.